Soil health of an Albaquults under integrated crop-livestock-forest system throug multivariate analysis (Research, Society and Development, 2020)
The objective of this work was to evaluate the health of a soil under an integrated crop-livestock-forest system through multivariate analysis of the physical, chemical and physical-hydric attributes of the soil. The experiment was carried out in a Albaquults with a sandy texture in the municipality of Alagoinha, PB, under the following consortia in a randomized block design: i) Br. Decumbens + Gliricidia sepium (BG); ii) Br. decumbens + Mimosa caesalpiniifolia (BS); iii) Br. decumbens + Tabebuia alba (BI); iv) Br. decumbens + Zea mays (LA); v) Brachiaria decumbens (BD). Samples (deformed and undeformed) of soil were collected to evaluate physical, physical-hydric and chemical properties of the soil in the layers of 0.0-0.1, 0.1-0.2 and 0.2-0.3 m. The averages were analysed using principal component analysis and Pearson's correlation (P